Bipartite tracking consensus of linear multi‐agent systems with a dynamic leader under signed digraph. Issue 15 (2nd September 2020) - Zhang, Xuxi; Han, Wenyan; Liu, Xianping
Abstract : This study is concerned with the bipartite tracking consensus problem for linear multi‐agent system over signed digraph, in which the leader agent owns a bounded control input that is unavailable to the followers. Compared with existing related works, the communication topology under consideration is allowed to be directed. Two kinds of distributed control protocols are proposed based on the relative states of neighbouring agents. By applying the graph theory, Lyapunov theory and adaptive control, some sufficient conditions for the bipartite tracking consensus are obtained. Finally, two simulation examples are provided to demonstrate the effectiveness of the proposed design methodology.